ANALISIS PENDORONG ALIH FUNGSI LAHAN IRIGASI (STUDI KASUS DAERAH IRIGASI KARANGLO) - Seto Sugianto Prabowo Rahardjo; Arum Pratiwi (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2014)
Regional Irrigation Irrigation Area Karanglo a trend of decreasing quantity and extent of paddy rice crop area or in other words the alleged land conversion, need to be aware that the national food supply of the province of East Java remains unfulfilled, according to the planned targets. To know further on the allegations of land use, study or analysis of these allegations should dilakukan.Salah one location that can be simulated in Irrigation Area is Karanglo Lumajang. Research examined using analysis of a wide range of technical and non-technical aspects. Where from a few aspects will be analyzed in accordance with a separate discussion. Analysis on the Legal Aspects will be brought closer to the Government Regulation no. 20 in 2006 and 82 and 83 of Article XII. Hydrology Aspect Analysis on will be analyzed on a regional water availability and irrigation needs. Analysis on the Agricultural Aspects will be analyzed for changes in the extent of irrigated area from 2001 to 2005. Analysis on the Social Aspects of culture will be brought closer to the results of field data collection through Quitioner. Analysis on the Economic Aspects will be brought closer to the results of field data collection through Quitioner and direct observation. From the legal aspect, the area irihasi Karanglo still not able to switch the function of aspects of hydrology, irrigation area Karanglo not a driver of land use because it has very adequate to discharge the availability of planting pattern of disesuaikan.Dari aspects of agriculture, indicated that the agricultural land, especially paddy fields experienced penurunan.Dari socio-cultural aspects, is a potential cause of land conversion irigasi.Dari economic aspects, the irrigation area Karanglo only indicated that the sugar cane and citrus commodities began to emerge as a result of the sugar factory Karanglo. The dominant factor that could potentially lead to conversion of irrigated land is economic, social and cultural aspects of each continuous with Indonesian law aspects that are not so tegas.Diharapkan with this study, the factors that may indicate the Irrigation land conversion, can be prevented